130 The pride of west midlands palliative care research: wm cares. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Coop, Hazel; Macfarlane, Mike; Doré, Matthew; Marlow, Clare; Prew, Sandra; Willis, Derek
Abstract : Background: Research is key for speciality development and higher medical training but there are well recognised barriers to participation in research within palliative care. The West Midlands Palliative Medicine Registrars recognised that lack of local structure and collaboration was contributing to trainees' difficulties in participating in research. Methods: The West Midlands Palliative Medicine Registrar group initiated a trainee-led collaborative, 'West Midlands Collaborative Actioning Research in End-of-life and Supportive Care' (WM CARES), which was launched in September 2016 with local stakeholder support. We hold monthly meetings at registrar training days, involving partners including the National Institute for Health Research (NIHR), local universities, palliative medicine consultants, speciality doctors and local providers of palliative care. We regularly update the wider palliative care community via newsletters, website and social media. Results: WM CARES has developed four research questions into working groups under consultant supervision. The WM CARES network enables larger, multi-site, high quality research which crosses the boundaries of any individual registrar's placement. To date, the group has presented six posters at national conferences and two journal articles are currently being prepared for publication. WM CARES has a mission to share local work, with collaboration being a central focus. This year the collaborative organised an inaugural conference, WM CARES PRIDE (Presentations in Research, Innovation, Development and Excellence) which showcased multidisciplinary research, audits and service developments from the region. There has been buy-in from the registrar body who recognise the opportunity to meet curriculum competences and explore research interests within a structured framework. Conclusion: WM CARES is an innovative and collaborative trainee-led network conducting high-quality research and raising the profile of research. It enables and enthuses Palliative Medicine Registrars and the wider multidisciplinary team to learn about and be involved in research activities, which will ultimately improve patient care.